Literature review of mobile banking and individual performance - Tam, Carlos (2017)
Tam, C., & Oliveira, T. (2017). Literature review of mobile banking and individual performance. International Journal of Bank Marketing, 35(7), 1042-1065. https://doi.org/10.1108/IJBM-09-2015-0143 ---%ABS1%